A Review of Shariah Auditing Practices in Ensuring Governance in Islamic Financial Institution (IFIs) – A Preliminary Study - Yahya, Yazkhiruni (Advances in Social Sciences Research Journal, 2018)
The main objective of shariah auditing[1] is to embrace the Maqasid As – Shariah (Objective of Islamic Principles) as well as to uphold the shariah principles in all business processes. Shariah auditing goes beyond the usual attestation and assurance for the financial statement, internal control and governance of firms and specified by the Central Bank of Malaysia (BNM) in Shariah Governance Framework (SGF, 2010), to be conducted by internal auditors. This paper discusses current practices of shariah auditing among Islamic Financial Institutions (IFIs) in Malaysia. Data reported in this paper is obtained through 15 semi-structured interviews conducted with chief internal audit, managers of internal audit department, shariah committee, external auditor and academicians. Findings indicated that the practices are still evolving where further developments and improvements are required focusing particularly on standardization of shariah audit framework and guidelines to design audit program for shariah auditing.In addition a proper design of competency framework for auditors performing shariah audit is highly recommended. [1] According to Shariah Governance Framework for Islamic Financial Institutions” (SGF, 2010) issued by the Central Bank of Malaysia (BNM), defined shariah audit as “the periodical assessment conducted from time to time, to provide an independent assessment and objective assurance designed to add value and improve the degree of compliance in relation to the IFI’s business operations, with the main objective of ensuring a sound and effective internal control system for Shariah (Islamic) compliance”.